Studi Pembuatan Minuman Serat Alami yang Kaya β-Karoten - Muhammad Said Siregar; Irfan Syukri Tbn; Herla Rusmarilin; Desi Ardilla (Jurnal Teknologi dan Industri Pertanian Indonesia, 2023)
Research on the study of producing rich beta carotene natural fibers beverage has been done by completely randomized design (CRD) with two replicates. The first factor was the ratio of water spinach stem and melinjo seed skin (S1 = 100:0, S2 = 75:25, S3 = 50:50, S4 = 25:75, S5 = 0:100). The second factor was the addition of carrots juice (W1= 30%, W2= 40%, and W3 = 50%). The parameters observed were fiber content, β-carotene content, water absorption index, oil absorption index, hedonic value of color, flavor and aroma. The statistical analysis was showed that the ratio of water spinach stem and melinjo seed skin provide highly significant effect (P ≤ 0.05) on fiber content, beta carotene content, water absorption index, oil absorption index, hedonic of flavor and aroma as well as had no significant effect (P 0.05) to  hedonic of color. The addition of carrot juice provides highly significant effect (P ≤ 0.05) on fiber content, beta-carotene content, water absorption index, oil absorption index, hedonic of aroma, color and flavor.